Assessing the impacts of coal-to-electricity transition in China’s regional power system and “2 + 26” cities - Lei Zhu; Zhuang Liang; Lizhong Zhang; Wenjun Meng; Xing Yao; Bin Su; Shu Tao (iScience)
Summary: Compared to air pollution, the Coal to Electricity (CtE) policy's impacts on the power system are less discussed. As China transitions to carbon neutrality, unstable wind, and photovoltaic (PV) units exacerbate power dispatching challenges amid increased heating loads. We simulate the electric heating and cooking loads in the ''2 + 26'' cities and integrate them into a provincial power dispatch model to assess CtE’s influence. CtE shows a slight CO2 reduction compared to heating with coal, potentially cutting emissions by up to two-thirds in high renewable energy scenarios. However, electricity prices fluctuate more in such scenarios, possibly increasing heating bills. CtE loads could increase the loss of load possibility in some provinces, especially with temperature drops and renewable capacity expansions. Overall, CtE places significant stress on the power system due to its additional loads and load fluctuations, requiring extra measures to ensure system adequacy amidst high wind and solar installations.